Religious Experience Behind Repeated Umrah: A Phenomenological Study of Umrah Pilgrims in Sumberlawang District, Sragen Regency - Annas Albara Sri Widyatama Albara; Abdul Rozaq (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − This study aims to analyze the motivations and religious experiences of pilgrims performing repeat Umrah in Sumberlawang District and identify their impact on the quality of worship and social life Method − The study used a qualitative descriptive approach with a phenomenological method. Data collection techniques were carried out through in-depth interviews and filling out a Google Form, with informants determined by purposive sampling. Findings − The results show that the primary motivation for repeat Umrah is driven by a belief in the great value of rewards, a spiritual longing for the Holy Land, and a desire to increase closeness to God. The religious experience felt includes inner calm, increased reverence, and a strong sense of spiritual encounter. The impact is seen in the improved quality of worship, a balance between life orientations between this world and the afterlife, and growing social awareness in the surrounding environment. Thus, repeat Umrah becomes a process of spiritual and social transformation that shapes the pilgrims' religious awareness more deeply.